Differentiation Learning Training in Projects as an Implementation Strategy for the Merdeka Curriculum at Yas'a Sumenep Middle School - Mochammad Yasir; Yamin Yamin; Wiwin Puspita Hadi; Purnomo Purnomo (CV. Media Digital Publikasi Indonesia, 2023)
One way of student-centered learning is by implementing differentiated learning. Although this differentiated learning is not new, teaching and learning activities are still rarely implemented, including in the Yas'a Sumenep Middle School, so there is a need for community service in the form of differentiation learning training in projects as a strategy for implementing the Merdeka Curriculum at Yas'a Sumenep Middle School. The purpose of this activity is (1) to provide knowledge to educators and stakeholders at Yas'a Sumenep Middle School about differentiation learning and projects; (2) to train the skills of Yas'a Sumenep Middle School educators in developing differentiation learning and projects to improve the quality of learning. The method in this activity includes (a) expository; (b) question and answer; (c) discussion; (d) demonstrations; (e) FGD. The results of community service activities obtained that knowledge of differentiation learning and projects were in the high category of 57 people and as many as 3 people in the medium category, as well as increasing skills in developing differentiation learning and projects in the high category of 52 people and as many as 8 people. The results of these activities can be concluded that the differentiation learning training activities in the project as an implementation strategy for the Merdeka Curriculum at Yas'a Sumenep Middle School can provide knowledge to educators and stakeholders about differentiation learning and projects in the Merdeka Curriculum, as well as to train skills educators in developing differentiation learning and projects to improve the quality of learning